Development of a model of medication review for use in clinical practice: Bristol medication review model - D. McCahon (BMC, 2021)
Abstract Background Medication review is a core aspect of medicine optimisation, yet existing models of review vary substantially in structure and content and are not necessarily easy to implement in clinical practice. This study aimed to use evidence from the existing literature to identify key medication review components and use this to inform the design of an improved review model. Methods A systematic review was conducted (PROSPERO: CRD42018109788) to identify randomised control trials of stand-alone medication review in adults (18+ years). The review updated that by Huiskes et al. (BMC Fam Pract. 18:5, 2017), using the same search strategy implemented in MEDLINE and Embase. Studies were assessed using the Cochrane risk of bias tool. Key review components were identified, alongside relevant clinical and health service outcomes. A working group (patients, doctors and pharmacists) developed the model through an iterative consensus process (appraisal of documents plus group discussions), working from the systematic review findings, brief evidence summaries for core review components and examples of previous models, to agree on the main purpose of the review model, overarching model structure, review components and supporting material. Results We identified 28 unique studies, with moderate bias overall. Consistent medication review components included reconciliation (26 studies), safety assessment (22), suboptimal treatment (19), patient knowledge/preferences (18), adherence (14), over-the-counter therapy (13) and drug monitoring (10). There was limited evidence from studies for improvement in key clinical outcomes. The review structure was underpinned by patient values and preferences, with parallel information gathering and evaluation stages, feeding into the final decision-making and implementation. Most key components identified in the literature were included. The final model was considered to benefit from a patient-centred, holistic approach, which captured both patient-orientated and medication-focused problems, and aligned with traditional consultation methods thus facilitating implementation in practice. Conclusions The Bristol Medication Review Model provides a framework for standardised delivery of structured reviews. The model has the potential for use by all healthcare professionals with relevant clinical experience and is designed to offer flexibility of implementation not limited to a particular healthcare setting.